Prevalence of Shiga toxin-producing Shigella species isolated from French travellers returning from the Caribbean: an emerging pathogen with international implications. (August 2015) - Gray, M.D.; Lacher, D.W.; Leonard, S.R.; Abbott, J.; Zhao, S.; Lampel, K.A.; Prothery, E.; Gouali, M.; Weill, F.-X.; Maurelli, A.T.
Abstract: Shiga toxins (Stxs) are potent cytotoxins that inhibit host cell protein synthesis, leading to cell death. Classically, these toxins are associated with intestinal infections due to Stx-producing Escherichia coli or Shigella dysenteriae serotype 1, and infections with these strains can lead to haemolytic–uraemic syndrome. Over the past decade, there has been increasing recognition that Stx is produced by additional Shigella species. We recently reported the presence and expression of stx genes in Shigella flexneri 2a clinical isolates. The toxin genes were carried by a new stx -encoding bacteriophage, and infection with these strains correlated with recent travel to Haiti or the Dominican Republic. In this study, we further explored the epidemiological link to this region by utilizing the French National Reference Centre for Escherichia coli, Shigella and Salmonella collection to survey the frequency of Stx-producing Shigella species isolated from French travellers returning from the Caribbean. Approximately 21% of the isolates tested were found to encode and produce Stx. These isolates included strains of S. flexneri 2a, S. flexneri Y, and S. dysenteriae 4. All of the travellers who were infected with Stx-producing Shigella had recently travelled to Haiti, the Dominican Republic, or French Guiana. Furthermore, whole genome sequencing showed that the toxin genes were encoded by a prophage that was highly identical to the phage that we identified in our previous study. These findings demonstrate that this new stx -encoding prophage is circulating within that geographical area, has spread to other continents, and is capable of spreading to multiple Shigella serogroups.